FROM THE GOLD PAN TO THE CONSTITUTION: A SOCIOLOGICAL AND LEGAL ANALYSIS OF ARTISANAL MINING IN BRAZIL - Edstron Secundino Santos, Júlio (Revista Gênero e Interdisciplinaridade, 2026)
This research analyzes artisanal mining (garimpagem) in Brazil as a structural phenomenon that transcends the extractive economic dimension, configuring itself as a persistent manifestation of land and social conflicts since the colonial period. Adopting an interdisciplinary approach that intertwines sociology, history, and law, the study investigates the metamorphosis of the garimpeiro — from the bandeirante adventurer to a subject of constitutional rights — and the state’s response to this activity, historically marked by an “administrative schizophrenia” that oscillates between revenue-seeking promotion and socio-environmental omission. The evolution of the regulatory framework is examined, with emphasis on the transition from the 1967 Mining Code to the 1988 Constitution, dissecting institutes such as the Artisanal Mining Permission (PLG) and the presumption of good faith in gold acquisition, recently overturned by the Supreme Federal Court. The critical analysis reveals how legislation, although formally inclusive, has been instrumented to “launder” illicitly sourced minerals, especially from Indigenous Lands. It concludes on the necessity for a new regulatory paradigm, grounded in a National Mineral Census and technological traceability, capable of distinguishing the artisanal worker from criminal organizations and integrating the activity into constitutional legality and global sustainability imperatives.